Demographic and referral analysis of a free chiropractic clinic servicing ethnic minorities in the Buffalo, NY area...2007 ACG RAC Conference award winning paper - Stevens GL (Journal of Manipulative & Physiological Therapeutics, 2007)
Objective: The overall purpose of this study was to determine the characteristics of patients presenting to a free clinic in an ethnic poor neighborhood and how they came to find out about this clinic. The objective of this study was to collect and analyze the demographic and referral information of a free clinic. Methods: Information was collected on patient age, race, sex, chief complaint, comorbidities, stages of care, zip code distribution, and referral source. The information collected was processed via Microsoft Excel (Microsoft Corp, Redmond, Wash) and compared with other studies in the literature. Results: The patient population (n = 256) was 65% (167) female and 35% (89) male. The race of most of the patients was African American (63%, 161). Lumbopelvic complaints were most common (57%, 147), followed by the neck (18%, 45) and thoracic complaints (7%, 17). Most conditions were chronic in nature (68%, 174), and most patients came from Buffalo zip codes (88%, 225) and/or were in poverty (78%, 199). Referrals were from patients (27%, 69), walk-ins (25%, 65), or the result of multiple marketing efforts (34%, 98). Discussion: The low back/extremity chief complaints, number of female patients, and number of walk-ins to this free clinic were higher than expected when compared with other studies. Conclusion: Most of the patient population seen at the Lighthouse Free Chiropractic Clinic was African American, female, from Buffalo, in poverty, and had lumbopelvic and/or chronic chief complaints. The largest number of referrals was from patients or walk-ins.